Incorporating Youtube Clips in the Classroom to Develop Students’ Cultural Understanding of American Culture - Maryani Maryani; Lewinna Aguskin (Bina Nusantara University, 2019)
This research investigated the use of YouTube video clips to develop the understanding of culture for students in American Culture class in a private university in Bandung. It sought to answer two research problems; first, students’ perceptions towards the use of YouTube video clips to develop their understanding of American culture; second, to what extent watching YouTube video clips supported the students’ understanding of American culture. The participants of this research were 61 undergraduate students of the English Department aged between 18-21 years. There were two types of data collection used in the research. First, data were taken from the weekly learning logs of the students containing three to five questions and one or two YouTube video clips, which were related to the topics of the textbook in the classroom. Second, the data from the open-ended questionnaire which were distributed to the students at the end of the semester. The qualitative data were analyzed using thematic analysis. The findings show that the students’ understanding of American culture has improved due to watching YouTube video clips that contain authentic cultural information from American life events and news shown in the clips. This research also provides useful information for teachers in teaching culture for a better learning process, which focuses on the use of YouTube video clips in the classroom.